2006
DOI: 10.1007/s00198-005-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone fracture prevalence in postmenopausal women suffering from pollen-allergy

Abstract: In conclusion, we found a high prevalence of low-energy fractures among pollen-allergic postmenopausal women which was associated with obesity. It is possible that the H1R antagonists compensate for both the negative effect of pollen-allergy and the adverse effect of inhaled corticosteroid treatment on bone fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In a study investigating whether pollen-allergy can affect bone mass and fractures in postmenopausal women, it was shown that H1R antagonists may compensate for the negative effect of allergy on bone fracture risk. 36 The use of an H1-antihistamine/mast cell stabilizer in a patient with systemic mastocytosis and extensive skeletal involvement, including elevated parameters of bone resorption, improved the bone parameters. 37 We confirmed that osteoblasts also express H1R and H2R 14,15 and showed that in primary osteoblasts their expression varied with the differentiation stage.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating whether pollen-allergy can affect bone mass and fractures in postmenopausal women, it was shown that H1R antagonists may compensate for the negative effect of allergy on bone fracture risk. 36 The use of an H1-antihistamine/mast cell stabilizer in a patient with systemic mastocytosis and extensive skeletal involvement, including elevated parameters of bone resorption, improved the bone parameters. 37 We confirmed that osteoblasts also express H1R and H2R 14,15 and showed that in primary osteoblasts their expression varied with the differentiation stage.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms. First, pollen allergy has in itself been linked to fracture risk [44], perhaps mediated through the effects of mast-cell-derived histamine. Second, side effects of pseudoephedrine include tremor and insomnia, which could increase the occurrence of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, obese patients are prone to developing allergic complications. 121,158 Mast-cell effector functions…”
Section: The Complement Systemmentioning
confidence: 99%